LISTENING TO FAST SPEECH: STRATEGIES AND PRACTICE - Teshaboyeva Nafisa Zubaydulla qizi Scientific advisor: Jizzakh branch of the National university of Uzbekistan named after Mirzo Ulug’bek. The faculty of psychology, the department of Foreign languages; Philology and teaching languages:English; Haydarova Sevinch Ummat qizi The faculty of psychology the department of Foreign languages: Philology and teaching languages: English, student of group 103-23 (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Understanding fast speech in any language is a common challenge for language learners and even native speakers in certain contexts. This article explores effective strategies to improve comprehension of fast speech, emphasizing the importance of phonetic reduction, context, and listening practice. By incorporating tools such as active listening, transcription exercises, and exposure to diverse audio materials, learners can enhance their ability to decode rapid speech patterns. This study aims to provide a framework for developing practical listening skills and building confidence in understanding fast-paced conversations.